Educational activities for primary healthcare workers: "educação permanente em saúde" and continuing education concepts in the day-to-day routine of primary healthcare units in São Paulo - Marina Peduzzi; Débora Antoniazi Del Guerra; Carina Pinto Braga; Fabiana Santos Lucena; Jaqueline Alcântara Marcelino da Silva (Faculdade de Medicina de Botucatu (Unesp), 2010)
The objective of this study was to analyze the educational activity practices among healthcare workers in primary healthcare units (PHUs) according to the concepts of "educação permanente em saúde" (EPS)¹ and continuing education (CE), healthcare and nursing work processes, teamwork and comprehensiveness. This was a cross-sectional study conducted in 10 PHUs in the municipality of São Paulo, through structured interviews with 110 key informants who represented all professional categories and teams at the PHUs. The interviews covered educational activities developed in 2005. The information was classified according to operational categories for each study variable, based on the theoretical framework. The workers reported 396 educational activities that demonstrated the complementary nature of the concepts of EPS and CE. In accordance with the perspectives of the Brazilian Unified Health System (SUS) and the transformation of healthcare practices, there is a need to expand the debate relating to EPS as public policy.